Making Progress Towards «Green» Propellants. Issue 8 (4th July 2018) - Dejeaifve, Alain; Fantin, André; Monseur, Lara; Dobson, Rowan
Abstract: Stabilisers are used in propellants to prevent the various effects such as oxidation, chain scission, energy loss and uncontrolled heat generation that are caused by homolytic and heterolytic cleavage of the weakest Nitrogen‐Oxygen bond of the nitrate ester functional group. Conventional stabilisers for nitrocellulose‐based propellants belong to a‐aromatic amines (e. g., diphenylamine, 4‐nitro‐N‐methylaniline…) or b‐aromatic urea derivatives (e. g., Akardite, centralite…) and are/or produce highly toxic and/or potentially carcinogenic species at some point during a propellant's lifetime. There is an obvious need for alternative stabilisers presenting a low toxicity profile and providing efficiencies similar to, or better than conventional stabilisers. This paper presents novel, environmentally friendly, efficient and readily‐available stabilisers for use in nitrocellulose‐based compositions. With REACh legislation (1907/2006), industry in Europe has made progress in using less toxic compounds, that are often more environmentally‐friendly. The aim of this work is to go beyond REACh and to anticipate the inclusion of other molecules that produce non‐ or less toxic daughter products and that can fulfil their role in the propellant's formulation. Abstract :